2018
DOI: 10.1007/s40618-018-0888-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of isoprostanes in polycystic ovary syndrome and its relationship with cardiovascular risk factors

Abstract: Patients with polycystic ovary syndrome have higher 8-isoprostanes levels and it is associated with several cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
2
1
Order By: Relevance
“…The present study shows statistically no significantly higher serum levels of 8-Isoprostane in women with PCOS compared with controls. The present study showed no evidence that the 8-Isoprostane used to evaluate oxidative stress in association with risk factors of CVD, which is not consistent with the commonly held notion that oxidative stress significantly contributes to CVD where there were no statistically significant between 8-Isoprostane with another parameter and the results of this study were that 8-Isoprostane levels showed negative weak correlate with most parameters in patients and this was not consistent with the previous study which showed presence association between 8-Isoprostane with higher CV risk in women with polycystic ovary syndrome [7] .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study shows statistically no significantly higher serum levels of 8-Isoprostane in women with PCOS compared with controls. The present study showed no evidence that the 8-Isoprostane used to evaluate oxidative stress in association with risk factors of CVD, which is not consistent with the commonly held notion that oxidative stress significantly contributes to CVD where there were no statistically significant between 8-Isoprostane with another parameter and the results of this study were that 8-Isoprostane levels showed negative weak correlate with most parameters in patients and this was not consistent with the previous study which showed presence association between 8-Isoprostane with higher CV risk in women with polycystic ovary syndrome [7] .…”
Section: Discussioncontrasting
confidence: 99%
“…Isoprostane is a group of compounds create via encouraging of free radicals for non-enzymatic peroxidation of arachidonic acid that is similar to prostaglandins [6] . Since Isoprostane's discovery by Roberts and Morrow in 1990 [7] , proposed many studies the good biomarker reliable for endogenous lipid peroxidation is the level of Isoprostane, consequently in vivo is important tool reverse the damage and oxidative status [6] . The high concentrations of 8-Isoprostane promote atherosclerosis and cardiovascular disease.…”
Section: Annals Of Tropical Medicine and Publicmentioning
confidence: 99%
“…Additionally, conditions such as cardiovascular, neurological, and respiratory disorders have been linked to high levels of IsoP. 12 Antioxidant defenses, physical defenses, and preventative and repair processes are all components of protective physiological mechanisms against oxidants. Antioxidants are chemicals that can neutralize, scavenge, or stop oxidants from forming.…”
Section: Oxidative Stress In Polycystic Ovarian Syndromementioning
confidence: 99%